La logica trascendentale del tempo. Comunicazione e trascendenza in Wolfgang Cramer e Karl Jaspers - Guidetti, Luca (Bollettino Filosofico, 2016)
According to Kant, time has a dual nature: on the one hand, it is the form of the external sense and, along with the space, it serves as a detection criterion of physical objects; on the other hand, it is the form of the internal sense, and, thanks to the schematism, it allows the construction of unitary images of phenomena. But the separation between the two conditions of knowledge, sensibility and intellect, does not guarantee the continuity between the physical and the phenomenical world, making enigmatic the unity of consciousness which should accompany all representations. From two different points of view, related to neokantism and to the philosophy of existence respectively, Wolfgang Cramer and Karl Jaspers try to overcome the Kantian difficulty, focusing on transcendentality of the act of consciousness rather than on its contents. It follows a twofold determination of the subject that, as shown by the same Kant, refers to examples from mathematical thinking. While to Cramer the pure intuition is the tangent of time that, through the act of thought, undergoes a process of integration in the experience, to Jaspers every act of consciousness is tied to an individual existence with its particular temporal dimension. In this sense, Cramer’s “integral of consciousness” does not guarantee the communication because it establishes only a difference in the absolute unity of the act, while, according to Jaspers, the real communication is unity in the difference, i.e. elevation of every single existence to the system of others “personal equations”. From this new logic of communication, related to time and transcendence of existence, arises a transcendental and not intellectual logic that Jaspers calls “rational a-logic”.